Pemanfaatan Mikrobiologi dalam Bioremediasi Tanah Pertanian Tercemar Pestisida : Kajian Literatur - Dorthi Ester Junita Daeli; Natalia Krisitiani Lase (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Soil pollution is a global problem with anthropological and natural sources. Pesticides are chemical compounds used to eradicate pests. Pesticides are chemical or biological agents that can weaken, paralyze, and kill pests. According to a report by FAO (2021), global pesticide use reaches more than 4 million tons per year, with Asia accounting for nearly 50% of total consumption. In Indonesia, data from the Ministry of Agriculture (2022) shows that pesticide use increased by 15% in the last decade. Unfortunately, the intensive and uncontrolled use of pesticides has triggered the accumulation of harmful residues in the soil, creating a serious threat to soil, environmental, and human health. The purpose of this study was to determine how the utilization of microbiology in the bioremediation of agricultural soil polluted with pesticides. The method in this journal article uses a library study (library research), namely a method with data collection by understanding and studying theories from various literatures related to the research. The results show that soil bioremediation to reduce pesticides in agricultural soils can be done by utilizing specific or local microorganisms (bacteria and fungi), or enzymatic degradation. Although in laboratory scale, many findings on soil bioremediation are available in the literature, only few data on real scale activities can be found.